Diversity of Crabs (Brachyura) and Association of Crabs (Brachyura) with Mangroves in Gerupuk Coast of Central Lombok - Kadek Indah Widya Sari; Abdul Syukur; Lalu Zulkifli (Jurnal Penelitian Pendidikan IPA, 2023)
Mangroves have a function as shelters, nurturing places, spawning grounds, and foraging places, and can be a habitat for wild animals. Brachyura is one of the mangrove biota associations whose lives are influenced by the existence of mangroves. Therefore, the purpose of this study is to determine the diversity of crabs (Brachyura) and the relationship between mangrove density and crab abundance (Brachyura) in the coastal mangrove area of Gerupuk Beach Central Lombok. The crabs (Brachyura) sampled were Brachyura contained in the observation plot, Brachyura on the surface of the substrate was taken by hand, while those in the hole were taken with the help of a shovel. The data obtained were then analyzed with the Pearson diversity index, association, and correlation coefficient. Furthermore, a simple linear regression analysis was carried out with the independent variable (x) mangrove density and the dependent variable (y) crab abundance (Brachyura). The results of this study obtained 7 species of Brachyura consisting of 6 species of the family Ocypodidae and 1 species of the family Grapsidae. The Brachyura diversity index at the research station was moderate to high with values between 1.7-4.0. Furthermore, there are 3 species of crabs (Brachyura) associated with 2 species of mangroves out of 7 species of Brachyura found. The linear regression equation y= 0.2619x + 0.0206 with a pearson correlation coefficient value (r) of 0.79 shows a strong relationship between the variable independek (x) mangrove density and the dependent variable (y) Brachyura abundance. The conclusion of this study is that Brachyura diversity in the Gerupuk Beach mangrove area is included in the medium category and there is a significant relationship between mangrove density and Brachyura abundance